Kombinasi Metode Rank Order Centroid (ROC) dan Operational Competitiveness Rating Analysis (OCRA) pada Sistem Pendukung Keputusan Penerimaan Kasir - Riski Ferita Wahyu; Hetty Rohayani; Valian Yoga Pudya Ardhana; Frieyadie Frieyadie; Adi Supriyatna; Desyanti Desyanti (PDSI, 2023)
A cashier is someone who, in carrying out his work, is responsible for processing payment transactions made by customers. In addition, cashiers can also serve cash and non-cash payments. The role of the cashier is needed in improving the quality of a company institution. In accepting the Cashier must meet several criteria such as Knowledge, Work Experience, Responsibility, Education, Loyalty, Status, and Age. So that in this problem requires a system that can provide the right solution such as Decision Support (SPK) to provide the solution found by using the Operational Competitiveness Rating Analysis or OCRA method in the process requiring data and cashier acceptance criteria. As for the results in the research on choosing the best cashier, the A5 alternative with a value of 1.9134 is Abdul Gani's name